Marginal propensity to consume and savings from a microeconomic perspective - Muñoz - Medrano, Janira Francisca; Brenes González, Humberto Antonio (Universidad Francisco de Paula Santander, 2024)
The objective of this article called “Marginal propensity to consume and save from a microeconomic perspective” was to estimate the marginal propensity to consume and save, by the workers of the JMC company, during the period from 2021 – 2022, to from their income and consumption. The research had a quantitative, non-experimental, correlational and cross-sectional approach. The methodology used to estimate the marginal propensity to consume was under a linear regression model, with Consumption (C) being the dependent variable and Income (I) being the independent variable. The coefficients of the constant and the slope (which represents the marginal propensity to consume) were estimated manually using Cramer's method of determinants. In turn, the estimates of the aforementioned coefficients were carried out using the programming language with a statistical approach R-Studio and the Office program Microsoft Excel. The marginal propensity to save was obtained by the difference of one minus the estimated coefficient of the marginal propensity to consume. The results showed a strong correlation between the variables under study (97.32%), as well as a high degree of explanation that income has on the level of consumption (94.71%), in addition, it was estimated that the marginal propensity to consume the workers of the JMC company which was (0.8427), with the savings being (0.1573).